Control of residual stress and distortion in aluminium wire + arc additive manufacture with rolling - Hönnige, Jan Roman; Colegrove, Paul A.; Ganguly, Supriyo; Eimer, Eloise; Kabra, S.; Williams, Stewart W. (Elsevier, 2018)
The aluminium alloy wire 2319 is commonly used for Wire + Arc Additive Manufacturing (WAAM). It is oversaturated with copper, like other alloys of the precipitation hardening 2### series, which are used for structural applications in aviation. Residual stress and distortion are one of the biggest challanges in metal additive manufacturing, however this topic is not widely investigated for aluminium alloys. Neutron diffraction measurements showed that the as-built component can contain constant tensile residual stresses along the height of the wall, which can reach the materials' yield strength. These stresses cause bending distortion after unclamping the part from the build platform. Two different rolling techniques were used to control residual stress and distortion. Vertical rolling was applied inter-pass on top of the wall to deform each layer after its deposition. This technique virtually elimiated the distortion, but produced a characteristic residual stress profile. Side rolling instead was applied on the side surface of the wall, after it has been completed. This technique was even more effective and even inverted the distortion. An interesting observation from the neutron diffraction measurements of the stress-free reference was the significantly larger FCC aluminium unit cell dimension in the inter-pass rolled walls as compared to the as-build condition. This is a result of less copper in solid solution with aluminium, indicating greater precipitation and thus, potentially contibuting to improve the strenght of the material.
Keywords: Neutron Diffraction; Surface Waviness; Promoted Dissolution; Vertical Rolling; Side Rolling; Pinch Rolling